Sustainable Swimming Pool Management Under Climate Stress: A Structured Review of Water-Energy Strategies in Europe - Deligianni, Athena; Gerasimina-Theodora Zapanti; Athanasios – Foivos Papathanasiou; Constantina Skanavis (Engineering Science & Technology, 2026)
The accelerating impacts of climate change-including intensifying heatwaves, recurrent droughts, and growing water scarcity-are placing increasing pressure on urban infrastructure, including recreational facilities such as swimming pools. The review considers both public and private swimming pool facilities, with particular relevance to urban and tourism-oriented pools that face increasing resource pressures under climate stress. While pools provide important public-health benefits by offering spaces for exercise, social interaction, and thermal relief, they are also highly water-and energy-intensive. This paper develops a conceptual framework for sustainable swimming pool management under climate stress, integrating the water-energy nexus, climate-resilient infrastructure, and sustainability transitions. A structured review of peer-reviewed literature published primarily between 2017 and 2026 (Google Scholar, GreenFILE, and PubMed) synthesizes technical, environmental, and policy evidence on water use, energy demand, and mitigation options in pool operations. The review predominantly draws on European case studies and policy contexts, reflecting climatic, regulatory, and infrastructural conditions common in Southern and Central Europe. The analysis shows that energy use-dominated by pool heating-represents the largest source of environmental impact, making renewable heating technologies such as solar thermal systems, photovoltaic-thermal collectors, and ground-source heat pumps among the most effective climate-mitigation measures. On the water side, backwash water recovery and reuse systems emerge as the single most powerful intervention, capable of reducing freshwater demand by up to 96% in well-designed systems, while low-cost efficiency devices provide essential baseline savings. By reframing swimming pools as adaptive urban infrastructures rather than discretionary amenities, the paper demonstrates how recreational water facilities can function as testbeds for integrated water-energy solutions, contributing to climate adaptation, resource efficiency, and long-term public-health resilience.